THE INFLUENCE OF DIFFERENT PLANT THICKNESS OF PORLOQ-1 COTTON VARIOUS ON DRY SUBSTANCE IN DEPENDING ON WATER-FOOD NORMS - Namozov Fazliddin Bakhromovich; Togaev Sukhrobjon Mirakhmatovich; Ismailov Dauletbay Uzakbaevich; Togaev Shuhrat Mirakhmatovich (Galaxy International Interdisciplinary Research Journal, 2021)
In the development of agro-techniques of Porloq-1 cotton variety in the conditions of typical gray soils of Tashkent region, pre-irrigation soil moisture is 70-70-65% relative to LFMC (limited field moisture capacity), seedling density is 80-90 thousand bushes / ha. weight 59.1 g,cotton yield 49.4 ts / ha, in the conditions of light gray soils of Syrdarya region Porloq-1 cotton before irrigation soil moisture 70-70-65% relative to LFMC, seedlings 100-110 thousand bushes When applying the norm of mineral fertilizers N260P182K130 kg / ha, the raw material of cotton per bush was 44.1 g, the cotton yield amounted to 46.2 ts / ha.